A new species-level taxonomy for Trapelia (Trapeliaceae, Ostropomycetidae) with special reference to Great Britain and the Falkland Islands. (26th January 2018) - ORANGE, Alan
Abstract: Trapelia is a small genus of worldwide distribution. Trapelia coarctata has long been regarded as a morphologically variable species and phylogenetic studies have suggested that it is non-monophyletic, or at least that species are frequently misidentified. The phylogenetic relationships of freshly-collected material of Trapelia were studied using ITS, mitochondrial SSU rDNA and to a small extent also beta-tubulin sequence data, together with chemical and morphological characters. Sequence data combined with morphology and chemistry confirm that the diversity of the genus at species-level has been underestimated. Trapelia coarctata is defined in a more restricted way and many specimens previously referable to this taxon are assigned to the reinstated species T. elacista, which differs in subtle morphological characters including a crack separating the thallus and apothecium in well-developed thalli. Trapelia involuta is reinstated as a separate, though closely related, species to T. glebulosa based on sequence data, morphology and chemistry, and is lectotypified. Trapelia collaris is a distinctive species described as new from Great Britain which has an extensive, cracked thallus with abruptly thickening marginal areoles arising on an inconspicuous prothallus, relatively small apothecia (rarely exceeding 300 µm diameter) and contains 5- O -methylhiascic acid as the major secondary substance. Trapelia obtegens is shown to include frequent non-sorediate morphs which have doubtless been misidentified as other species. The number of species of Trapelia considered to occur in Europe is thus raised from five to eight. The genus is newly reported for the Falkland Islands where seven species occur: T. coarctata, T. placodioides, T. sitiens sp. nov. (with a thin, extensive thallus, sessile apothecia, 5- O -methylhiascic acid as the major secondary substance and the presence of conidiomata), T. tristis sp. nov. (with relatively small apothecia up to 460 µm diameter, presence of gyrophoric acid as the major substance and an absence of conidiomata) and three unidentified species represented by very sparse material. All the species studied, with the possible exception of the three unidentified species, can usually be distinguished by morphological features, particularly the method of development of the thallus and the shape and distribution of the areoles, but morphological variation in response to microhabitat variation is likely to make a proportion of specimens difficult to assign to species in the absence of sequence data.